Analysis of Good Corporate Governance Implementation in Improving Banking Performance in Gorontalo Province - Hais Dama (AIBPM Publisher, 2018)
Good Corporate Governance is a process and structure that is used to direct and manage business and company affairs in order to increase business prosperity and corporate accountability with the main goal of realizing shareholder value in the long term while taking into account the interests of other stakeholders. The objectives of this study include ( 1) To analyze how the implementation of Good Corporate Governance in improving banking performance in Gorontalo Province is. (2) To identify constraints in the implementation of Good Corporate Governance in improving banking performance in Gorontalo Province. (3) To find efforts to minimize obstacles in the implementation of Good Corporate Governance in improving the performance of banks in Gorontalo Province. The research is designed to be carried out for a period of one year using descriptive qualitative research methods with stages of activities including (1) Identification of problems in the implementation of Good Corporate Governance in improving banking performance in Gorontalo Province, (2) Analysis of the implementation of Good Corporate Governance in improving banking performance in Gorontalo Province, (3) Selection of alternative problem solving in the implementation of Good Corporate Governance in improving the performance of Banking in Gorontalo Province, (4) Designing a model for implementing Good Corporate Governance in improving banking performance in Gorontalo Province. The technique of collecting data is used by means of observation, interviews, documentation and implementation of the FGD which aims to obtain data in supporting the final results of the study. The results of the study show that the implementation of the Good Corporate Governance banking system in Gorontalo Province in order to improve performance includes, (1). the status of the bank as a branch office and sub-branch office etc. is an obstacle and a problem that makes the application of the principles in Good Corporate Governance not optimal. (2). There needs to be awareness and willingness from the directors, shareholders, and bank management to raise the status of the subsidiary bank to branch office, (3). The failure of the implementation of Good Corporate Governance in banking in Gorontalo Province has led to the Bank's performance evaluation by banks is not optimal. (4). Banking performance that is not optimal can be seen from the very high LDR ratio of up to 200%. (5). This ratio is not very contributing to regional economic growth, especially Gorontalo Province. Keywords: Good Corporate Governance, Banking performance.